Political Sociology in South Korea Engagement with ASEAN: A Constraint of Habit - Ratih Indraswari; Maresha Caroline Wijanto (Indonesian Journal of Sociology, Education, and Development, 2026)
For the last three decades, the Republic of Korea has actively engaged with ASEAN by participating in major ASEAN-led dialogue platforms. However, existing scholarship argues that South Korea’s engagement with ASEAN is often overshadowed by relations with major powers, particularly the United States, and by issues concerning North Korea. Building on this observation, this research investigates the domestic political factors that sustain U.S. primacy in South Korean foreign policy through the lens of foreign policy habit. Drawing on identity formation and the distribution of power amongst elites, the study argues that historical experiences, especially the Korean War and the enduring North Korean threat, have shaped a pro-U.S. political identity among South Korean elites. This identity is reproduced amongst the elite, creating path-dependent beliefs and practices that put primacy on the U.S. in foreign policy decision-making.